A STUDY ON TAX PLANNING FOR SALARIED EMPLOYEES AND STRATEGIES FOR TAX SAVING SCHEME (International Journal of Food and Nutritional Sciences, 2022)
A tax plan is about that particular person’s income for that year. Tax planning is not tax avoidance but saving tax without violating any legal rules. Tax planning is very important in the life of every salaried employee. As far as India is concerned, salaried employees have to pay more tax next to businessmen. The government provides many allowances, deductions and investment schemes for salaried employees who pay tax. The salaried employees should design their own investment and saving schemes according to their needs for tax saving .Tax planning is important when it comes to tax saving. Financial planning is an essential part of tax planning. Tax planning helps to reduce the tax liability of every salaried employee so all salaried employees should be aware advantages of exemptions and deductions. Primary and secondary data collection method was used for this study and random sampling method was applied to collect data.